Undergraduate students in times of HIV: testing context - Tania Maria Cemin Wagner; Alice Maggi; Carla Tessari de Souza; Ricardo da Silva de Souza (Interação em Psicologia, 2010)
The aim of this study was to better explain the attitudes of university students regarding the decision to undergo HIV testing and the possibility of taking part in studies on vaccinations, by categorizing these students from a socio-demographic viewpoint. The participants were 645 students from different undergraduate courses at a university in the South of Brazil – mean age 25.32 years, 442 (68.5%) were female and 202 (31.3%) were male). A questionnaire was administered, with 33 multiple choice questions, covering socio-demographic data, as well as objective and hypothetical situations. The results clearly showed that 197 (30.5%) of the participants had been tested for HIV. One met a statistical significant association (Exact of Fisher = 0,000) and a high correlation (0,000) between having been tested and to have thoughts on the same. The study revealed the need for university spaces to provide for the possibility of discussions and specific campaigns.